The Baptism of Galatians 3 27: A Contextual Approach - Hunn, Debbie (2004)
Presents a contextual interpretation of the meaning of baptism as used by Apostle Paul in Galatians 3:27 of the New Testament. Examination on the views of Paul on baptism in the context of the Spirit; Significance of baptism in the Christian faith; Contention that the baptism meant by Paul in this verse is water baptism; Discussion on the interpretations of Bible scholars of the verse; Explanation that the verse emphasizes the unity of Christians due to baptism and that Jesus Christ does not regard distinctions as the world does.
Keywords: Bibel; Baptism; Baptism in the Bible; Bible. Galatians; Christianity; Paul, The Apostle, Saint